Analisis Puisi “Aku Mencintaimu Diam-Diam” Karya Anwar Maulana (Khirani: Jurnal Pendidikan Anak Usia Dini, 2023)
Poetry is a form of fiction that contains an implied meaning. Poetry can motivate writing lovers, especially readers who are interested in reading something that has meaning and meaning implied in it from a poem through analysis. Based on previous understanding or exposure, the author is interested in conducting a study, namely analyzing Anwar Maulana's poem entitled "I Love You Secretly" using an intertextual approach. The results of the analysis of the reading of this poem include heuristic reading, hermeneutic reading, matrix determination, model and meaning. The matrix in the poem "I Love You Secretly" is I love you secretly, the model is relationship and romance, the meaning of this poem is sincerity and eternal love which cannot be seen from a person's physique but seen from the sincerity of his heart. The results of the study of the intertextual relations of the two poems include the relationship between the structure of the poem, the relationship of the matrix, the relationship of the model, the relationship of meaning, and the hypogram.